Soil invertebrates in an Ultisol soybean agroecosystem amended with urea-enriched cogongrass biochar prepared with Sargassum extract - LAODE MUHAMMAD HARJONI KILOWASID; AL’ADLIN AL’ADLIN; SYAMSU ALAM; TRESJIA CORINA RAKIAN; NINI MILA RAHNI; ROBIATUL ADAWIYAH (Society for Indonesian Biodiversity, 2026)
Abstract. Kilowasid LMH, Al’adlin, Alam S, Rakian TC, Rahni NM, Adawiyah R. 2026. Soil invertebrates in an Ultisol soybean agroecosystem amended with urea-enriched cogongrass biochar prepared with Sargassum extract. Biodiversitas 27 (1): d270116. https://doi.org/10.13057/biodiv/d270116. Soil invertebrates are widely used as bioindicators to assess changes in ecological functioning under different management practices. However, information on the influence of enriched biochar amendments on the community of invertebrates in tropical Ultisol remains limited, particularly in the context of reducing dependency on synthetic fertilizer through organic-based management. Therefore, this study aimed to evaluate the interactive effects of cogongrass (Imperata cylindrica) biochar doses and urea concentrations dissolved in Sargassum seaweed extract on the abundance and diversity of soil invertebrates in an Ultisol-based soybean agroecosystem. A split-plot experiment was conducted using three biochar doses (0, 5, and 10 t ha⁻¹) and four urea solution concentrations (0, 5, 10, and 20%) as main plots and subplots, respectively. Soil-surface invertebrates were collected using pitfall traps, while soil-living invertebrates were sampled through hand-sorting and monolith methods, and identified at the family level. The results showed that biochar and urea amendments significantly restructured the community of soil invertebrates, with contrasting responses between soil-surface and soil-living groups. Biochar dose primarily influenced surface-active invertebrates, and urea concentration affected specific soil-living taxa, with interaction effects observed for selected functional groups. Higher biochar doses increased community diversity, as reflected by higher Shannon-Wiener and lower Simpson indices, while moderate urea concentrations supported the highest taxon richness. Optimized biochar-urea combinations enhanced the abundance of predatory invertebrates, particularly ants (Formicidae), without reducing overall taxonomic diversity. These findings show that urea-enriched cogongrass biochar prepared with Sargassum extract can improve soil ecological functioning through beneficial restructuring of the community of invertebrates, supporting its potential role in sustainable nutrient management and biodiversity-based restoration of degraded tropical Ultisol agroecosystem.